Antibacterial Activity of the Vancomycin and Cefotaxime-Incorporated Total Etch Adhesive System - An In Vitro Study - Rangareddy M. S; Wahed Md Abdul; Kumar B. Shravan; Karteek Basa Srinivas; Reddy Chavva Lakshmi Charan (Wolters Kluwer Medknow Publications, 2024)
BackgroundMarginal failure at the resin dentin interface promotes biofilm formation, which further leads to secondary caries and hypersensitivity. This likelihood also increases if residual bacteria are present following cavity preparation. In order to achieve a proper biological seal without jeopardizing bonding, efforts were made to functionalize the adhesive system with antibacterial activity. Aim and objectives: To appraise the antibacterial activity of a total-etch adhesive system against S. mutans with and without incorporation of antibiotics Vancomycin and Cefotaxime. Materials and MethodA commercially available 5th-generation total-etch bonding agent (Te-Econorm) was used. S. mutans broth had been standardized and streaked over Muller-Hinton agar culture medium and round wells about 6 mm in diameter were made in the centre of the agar plates. Each experimental group comprised 10 samples, which include: Group 1 - 30µg Cefotaxime, Group 2- 30µg Cefotaxime + Bonding agent, Group 3- 30µg Vancomycin, Group 4- 30µg Vancomycin + Bonding agent, Group 5- Bonding agent, and Group 6- No material. Inoculated culture plates were examined for the zone of inhibition after incubation at 37° C for 24 hours. ResultsThere was a significant difference in the mean diameter of zone of inhibition (p=0.000), with the maximum exhibited by Group 4, followed by Group 3 and Group 2. The least zone of inhibition was exhibited by Groups 1 and 5. The negative control showed no zone of inhibition. ConclusionThe combination of Vancomycin and bonding agent had superior antibacterial activity against S. mutans in comparison to cefotaxime and bonding agent.